Teorias contextualistas em epistemologia - Ketzer, Patricia (2010)
Historically epistemology has defined knowledge as universal and infallible. However, tradition has not accounted for solving in a sufficiently satisfactory way the issues posed by skeptics such as the question of existence of an external world outside the mind, the argument from illusion and from error, among others. Consequently, reformulations of the concept of knowledge have been proposed, developing new approaches to Epistemology. Externalist theories are found among the new approaches proposed, whereby externalism is the defense that the one who believes does not need to have access to the reasons that justify his/her beliefs. Moreover, some of these new proposals defend that knowledge is fallible, and that our beliefs are nullified and in need of revision, that is, they are theories of fallibility. Contextualism is to be found among the new epistemic theories. Contextualist theories hold a series of divergent formulations, but they all agree that knowledge is relative to the context that it is inserted and in which it is discussed. Contextualists accuse traditional epistemology of ignoring the different contexts in which there is knowledge by assuming as a standard a highly strict epistemological context that regulates knowledge in any circumstance. According to defenders of contextualism, the simple fact of considering the contextual differences would eliminate skepticism. This works intends to show that contextualism corresponds to a new way of comprehending knowledge in epistemology, and in doing so, it reformulates the main concepts of tradition. Contextualism comprehends knowledge in a practical way, defending that the social norms should be taken into account in epistemology, and especially it opposes skeptical objections.